Classroom Listening Assessment: Strategies for Speech-Language Pathologists - Johnson, Cheryl DeConde (Seminars in Speech and Language, 2012)
Emphasis on classroom listening has gained importance for all children and especially for those with hearing loss and special listening needs. The rationale can be supported from trends in educational placements, the Response to Intervention initiative, student performance and accountability, the role of audition in reading, and improvement in hearing technologies. Speech-language pathologists have an instrumental role advocating for the accommodations that are necessary for effective listening for these children in school. To identify individual listening needs and make relevant recommendations for accommodations, a classroom listening assessment is suggested. Components of the classroom listening assessment include observation, behavioral assessment, self-assessment, and classroom acoustics measurements. Together, with a strong rationale, the results can be used to implement a plan that results in effective classroom listening for these children.
Keywords: classroom listening; IDEA; Response to Intervention; functional assessment; hearing assistance technology; communication plan